Exploring and Identifying the Potential for Economic Empowerment: A Service in Alue Naga Village - Yunus, Mukhlis; Kesuma, T. Meldi; Siregar, M. Ridha; Ramli, Fahmi Irwan; Umuri, Khairil; Nisva, Raisa Ullya; Humaira, Radhia; Silvia, Vivi; Ramida, Ramida (Jurnal Pengabdian Bakti Akademisi, 2024)
This community service project in Alue Naga Village, Banda Aceh, aimed to explore and identify its economic empowerment potential, focusing on oyster farming and ecotourism. Despite the villages rich natural resources, such as a preserved mangrove ecosystem and high-quality oysters, these remain underutilized due to limited infrastructure, poor resource management skills, and marketing challenges. The project used a Service-Learning (SL) approach, involving multiple stakeholders including local government, researchers, and community members. Key activities included socialization, education, and training for fishermen, MSMEs, women, and youth. The project delivered results of prior studies and developed sustainable strategies for local economic empowerment. The results showed significant potential for oyster farming and ecotourism development, though improvements in infrastructure and market access are needed. Villagers showed high engagement, particularly in developing processed oyster products like crackers and nuggets. Collaboration between stakeholders enabled a comprehensive approach to economic empowerment, addressing both social and environmental factors. This project offers a replicable model for other coastal villages in Indonesia, demonstrating that strategic planning, community engagement, and multidisciplinary collaboration are essential for sustainable village development. Additionally, the initiative contributed to achieving Sustainable Development Goals (SDGs) such as No Poverty, Decent Work and Economic Growth, and Life Below Water, highlighting its long-term benefits for the community.